Scrap Rubber and Asphalt for Ballast Layer Improvement - M. Setiawan, Dian (International Journal of Integrated Engineering, 2019)
The use of scrap rubber from waste motorcycle tire and asphalt materials is expected to improve the quality of the ballast structure. The objective of this paper is to analyze the characteristics of ballast mixture with additional scrap rubber (uniformed size 3/8â€ and graded size No.4, 3/8", 1/2", 3/4", 1") and asphalt materials through compressive strength test by Micro-Computer Universal Testing Machine (UTM). The samples are made in a ballast box with a size of 40 cm x 20 cm x 30 cm. The parameters of this research are the vertical deformation, the aggregate abrasion, and the elastic modulus of the ballast layer. It could be concluded that asphalt 2% able to improve the stiffness of the ballast layer so it could minimize the vertical deformation and increase the ability to retain the loads up to 28%. Moreover, the use of scrap rubber materials, especially with various sizes between No.4, 3/8", 1/2", 3/4", 1" combined with 2% asphalt could reduce the ballast abrasion up to 57%. However, the use of scrap rubber material could reduce the stiffness of the ballast layer which leads to a decrease in the elastic modulus ranging from 50% to 60%. While on the other hand, asphalt material could improve the stiffness of the ballast layer so that the elastic modulus could be increased up to 21%.